Ultrasensitive hybridization analysis using fluorescence correlation spectroscopy. - Kinjo, M (1995)
The hybridization of fluorescently tagged 18mer deoxyribonucleotides with complementary DNA templates was analysed by fluorescence correlation spectroscopy (FCS) in a droplet under an epi-illuminated fluorescence microscope at the level of single molecules. The interaction can be monitored by the change in the translational diffusion time of the smaller (18mer) primer when binding to the bigger (7.5 kb) DNA containing the complementary sequence. The hybridization process in the presence of template M13mp18 ssDNA was monitored in a small volume (2 x 10(-16)I) at various temperatures. The Arrhenius plot of the association rate constant shows that the activation energy was 38.8 kcal/mol, but the hybridization process may involve several components. The titration experiment suggested that approximately 2 primers can be associated with one template DNA at 40 degrees C. Results of a simple homology search for the sequences complementary to the primer indicate the existence of additional sites of lower specificity.